ADVANTAGES OF USING INTERACTIVE TECHNOLOGIES IN TEACHING THE «ELECTRICITY AND MAGNETISM» SECTION IN HIGHER EDUCATION - Bazarbaev, Zinatdin Bisenbaevich (SCIENCE and SOCIETY, 2026)
In modern education, increasing students' knowledge of physics through the organization of physics lessons based on interactive technologies remains one of the most pressing aspects of education today. To increase the efficiency of today's modern educational process, the processes of developing and implementing new technologies continue; one such highly effective method is the «Flipped Classroom» method. The article provides information on the advantages of using the «Flipped classroom» method in teaching the «Electricity and Magnetism» section in higher education. Opinions are also expressed regarding the effectiveness of interactive technologies in teaching the topic «Coulomb's Law.»
Keywords: interactive technology; «Flipped classroom; » information; education; students; educational process; knowledge; skills and abilities; educational goals; non-traditional education; traditional education.